The Cambridge companion to Rabindranath Tagore - Chaudhuri, Sukanta, 1950- (Cambridge University Press, 2020)
"The corpus of Rabindranath Tagore's work is immense in scope, form and variety. His writings on nationalism, movements, society, governance, state, and welfare offer opportunities to students and scholars to understand the history and politics of colonial India, as well as to study India and the world in a contemporary context. His poems, verses, songs, stories and plays are numerous, offering further scope of research and study to students of cultural studies, literature, and the arts. His works are characterized by their timelessness and are curiously applicable to situations and contexts through ages. Despite this enormity of his creations, however, he has been understudied in the global discourse on literature and the arts. This volume brings together eminent Tagore scholars to create a comprehensive book that sits very well within the Cambridge Companions to Literature series. The volume editor, Emeritus Professor Sukanta Chaudhuri, is a stalwart in Tagore studies and is renowned globally for his scholarship. This volume is a first of its kind attempt to initiate and continue a discussion of Tagore studies globally"--